Seismic refraction and wide-angle reflection exploration by JARE-43 on Mizuho Plateau, East Antarctica - Miyamachi, Hiroki; Toda, Shigeru; Matsushima, Takeshi; Takada, Masamitsu; Watanabe, Atsushi; Yamashita, Mikiya; Kanao, Masaki (National Institute of Polar Research, 2003)
P(論文) The 43rd Japanese Antarctic Research Expedition (JARE-43) carried out seismic exploration experiments on Mizuho Plateau,East Antarctica,in the austral summer season of ,2001-2002. The exploration was composed of seven large explosions and 161seismic stations distributed along the 151 km-long seismic line.The first arrival time data are analyzed by a refraction method.It is found that the ice sheet is composed of two layers:the upper layer with P wave velocity of 2.7-2.9 km/s has thickness of 35-45 m,and the lower layer with P wave velocity of 3.7-3.9 km/s continues to the bedrock.Lateral velocity variation in the upper-most crust is revealed:P wave velocity for the upper-most crust in the southern and central parts is 6.1-6.2 km/s and that in the northern part is5.9 km/s. This result implies that the geological boundary observed along the coast in the Lu tzow-Holm Bay and Prince Olav Coast regions possibly continues to the inland area.The S wave velocity is also obtained to be roughly 3.5km/s for the whole upper-most crust.Travel time analysis of two distinct reflection phases shows two horizontal reflecting planes located at 19 and 40km depth; the latter corresponds to the Moho discontinuity. departmental bulletin paper